Perfil sócio-econômico dos coletores de resíduos sólidos recicláveis no município de Goioerê/PR - Carvalho, Márcia Aparecida de (2011)
With the aim of charting a socio-economic profile of recyclable solid waste in the Goioerê city – Paraná State, and also identify the economic motivations that lead the recyclable waste collector of this city to choose for this work and verifying your consciousness and perception about the environment, this research was conducted with a quantitative methodology through field observations and application of the questionnaire. Some collectors difficulties were observed when it comes to evaluate their own importance for society and the environment - even having some basics concepts about the benefits of its activity to the environment, this was not reflected in their attitudes practiced in daily life, both in waste collection and storage of collected material and on the allocation of that has no commercial value. These problems show that society in general and the public authorities have a lot to do to modify such attitudes and make the activity practiced by collectors most beneficial to the environment, for the collective one and for themselves, not being seen only as income source.